Exploring the Multiplex Architecture of Supply Networks - Kim, Myung Kyo; Narasimhan, Ram (International Journal of Supply Chain Management, 2019)
This paper attempts to provide quantitative and statistically significant evidence on the multiplex nature of a multi-tier supply network. The unique primary data consisted of component-level supply networks is analyzed to examine the interrelationships among their architectural properties based on various network tie types. All the supply network partners’ bidirectional responses stretching from an OEM to its raw materials suppliers are collected and treated as directed-valued in the analysis. Our findings collectively show that different types of supply network ties across multiple tiers of supply chain partners shape different supply network architectures.